1999
DOI: 10.1063/1.477924
|View full text |Cite
|
Sign up to set email alerts
|

A complete basis set model chemistry. VI. Use of density functional geometries and frequencies

Abstract: The recently introduced complete basis set, CBS-Q, model chemistry is modified to use B3LYP hybrid density functional geometries and frequencies, which give both improved reliability (maximum error for the G2 test set reduced from 3.9 to 2.8 kcal/mol) and increased accuracy (mean absolute error reduced from 0.98 to 0.87 kcal/mol), with little penalty in computational speed. The use of a common method for geometries and frequencies makes the modified model applicable to transition states for chemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
2,214
2
26

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,571 publications
(2,285 citation statements)
references
References 27 publications
43
2,214
2
26
Order By: Relevance
“…[42,43,[45][46][47] The mean absolute deviation in the G2 test set is reported to be 0.87 kcal mol À1 . [42] The accuracy in predicting kinetics of pericyclic reactions is most important to our study. Guner et al evaluated this for 11 different reactions [46,47] and CBS-QB3 was found to have a mean absolute deviation value of 1.9 and a standard deviation of 1.6 kcal mol À1 , when compared to experimentally determined activation enthalpies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[42,43,[45][46][47] The mean absolute deviation in the G2 test set is reported to be 0.87 kcal mol À1 . [42] The accuracy in predicting kinetics of pericyclic reactions is most important to our study. Guner et al evaluated this for 11 different reactions [46,47] and CBS-QB3 was found to have a mean absolute deviation value of 1.9 and a standard deviation of 1.6 kcal mol À1 , when compared to experimentally determined activation enthalpies.…”
Section: Methodsmentioning
confidence: 99%
“…The highly accurate multicomponent complete basis set (CBS-QB3) [42,43] method of Montgomery, Ochterski, and Peterson was used for obtaining energetics in the gas phase, using the Gaussian 03 [44] program. CBS-QB3 uses coupled cluster (CCSD(T)) energies, which are extrapolated to the basis-set limit using MP2 and MP4 energies and empirical corrections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a general problem with ab initio Hessians of finite accuracy and has been described previously. 44 The one-dimensional energy dependencies plotted in Figure 2 provide shallow potential wells/plateaus for the minima. For the rotational barrier of CO 2 -the computations seem to converge to the value of about 4 kcal/mol obtained for the best basis set (6-31++G**), while for NH 3 + the barrier is lower and practically disappears for the best basis.…”
Section: L-alanine Torsional Motionsmentioning
confidence: 99%